1999
DOI: 10.1097/00007890-199904270-00001
|View full text |Cite
|
Sign up to set email alerts
|

Portopulmonary Hypertension and the Liver Transplant Candidate

Abstract: The management of the liver transplant (OLT) candidate with portopulmonary hypertension (PPHTN) has dramatically changed in the past 3 years. Careful preoperative evaluation with functional characterization of right ventricular function plays a critical role. The pulmonary vascular response to epoprostenol infusion serves as a deciding factor for OLT candidacy. Careful perioperative attention to avoid right ventricular failure from acutely elevated pulmonary artery pressures or sudden increases in right ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 36 publications
2
87
0
2
Order By: Relevance
“…When the MPAP is > �0 mmHg, the condition becomes life threatening and can mmHg, the condition becomes life threatening and can mmHg, the condition becomes life threatening and can lead to right ventricular failure and hypoxemia. If surgery is contemplated, pulmonary pressures must be optimized usually with intravenous epoprostenol [28] , but sildenafil or bosentan have also been tried perioperatively.…”
Section: Pulmonary Conditionsmentioning
confidence: 99%
“…When the MPAP is > �0 mmHg, the condition becomes life threatening and can mmHg, the condition becomes life threatening and can mmHg, the condition becomes life threatening and can lead to right ventricular failure and hypoxemia. If surgery is contemplated, pulmonary pressures must be optimized usually with intravenous epoprostenol [28] , but sildenafil or bosentan have also been tried perioperatively.…”
Section: Pulmonary Conditionsmentioning
confidence: 99%
“…2 As a consequence, many authors consider that severe portopulmonary hypertension (i.e., mean pulmonary artery pressure [MPAP] above 40 mm Hg) represents a contraindication for liver transplantation because it would carry an unacceptable mortality rate. 3 Because portopulmonary hypertension is frequently asymptomatic until mean pulmonary pressure exceeds 40 mm Hg, most authors recommend systematic screening at evaluation. Several studies have suggested that Doppler echocardiography, when performed during pretransplantation evaluation, is a useful noninvasive tool to document or exclude portopulmonary hypertension, [4][5][6] even though this technique carries a significant proportion of false positives.…”
mentioning
confidence: 99%
“…This finding is slightly higher than previously reported rates of 2-12% of patients undergoing evaluation for liver transplant. 22 Of patients with pulmonary hypertension, almost three quarters had some grade of IPS, although no overall difference in mean PASP was seen in patients with and without IPS. This discrepancy could be explained by the relatively small study sample size and higher degrees of PASP in patients with IPS.…”
Section: Discussionmentioning
confidence: 90%